Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atlântica, Brazil - Paredes-Munguia, Williams; Teixeira, Renato Augusto (Zootaxa, 2019)
Among South American pholcid genera, Mesabolivar Gonzales-Sponga, 1998 is the largest with 94 species (World Spider Catalog 2019). Over the last two decades, most of these species were described from forest and caves (Huber 2000, 2018a; Huber 2005; Machado et al. 2007a,b,c, 2013). Besides a well-resolved taxonomy, many Mesabolivar species’ natural history is described. Such kind of information has been used both to quantify the spider diversity in caves and to hypothesize how species arrived and diversified into or around caves (Huber 2018b). Here, we describe the female of Mesabolivar guapiara (Huber 2000) for the first time, illustrating the diagnostic features of both sexes and new distributional data are provided from caves and their surroundings.